Synthesis, Anticancer and Anti-HIV Activities of Some Nitrogen Mustard Type Nucleoazasteroids - Jindal, D.P.; Pathak, Devender (Asian Journal of Chemistry, 2010)
17a-(2-Hydroxyethyl)-17a-aza-D-homo-4-androsten-3-one (1)have been synthesised by the reaction of 17a-aza-D-homo-4-androsten-3-one with ethylene chlorohydrin and 4-(2-hydroxyethyl)-4-aza-5a-androstan-17β-ol (3) have been prepared by the reaction of4-aza-5a-androsten-17β-ol with ethylene chlorohydrin. The compound1 on treatment with mesyl chloride and then treatment with10% sodium carbonate gave 17a-(2-chloroethyl)-17a-aza-D-homo-4-androsten-3-one (2). The compound 3 on treatment with thionylchloride gave 4-(2-chloroethyl)-4-aza-5α-androsten-17β-ol (4).